Corações em pedras: configurações criativas e identitárias do/a educador/a emocional na cidade de Queimadas-PB - Lima, Maria das Graças de (2023)
Doctoral thesis carried out in the popular education line of the education program at the Federal University of Paraíba. The thesis studied the circumstances in which the teaching profession and the formative and collaborative practices carried out in the context of the Department of Education in the city of Queimadas-PB, enable the construction of the identity of the emotional education teacher and the creative processes that emerge in the development of the socio-emotional competencies necessary for this role. It is based on the assumption that the world of work is an important formative space as it enables learning to take place in and through immersion in everyday school practices and reflections, and that continuing education allows innovative creative and identity processes to emerge in relation to Emotional Education. The theoretical dimension of the research is fundamentally based on Rolando Toro's theory on the construction of identity processes. The methodological dimension is organized around a case study, which involves a group of teachers who are responsible for teaching Emotional Education in the municipal school system in the city of Queimadas-PB. In addition to semi-structured interviews, the virtual space of the mobile device - specifically the WhatsApp instant messaging application - was used as an information strategy, since the group of teachers is part of this virtual space, exchanging ideas and experiences. It was concluded that the teaching identity of the Emotional Educator is constituted individually and collectively from a set of shared knowledge, experience and values. The results of the thesis allowed us to affirm that the creation of the identity processes of emotional educators is made up of elements such as experience, an enriched environment, motivation, imagination and a critical attitude.